2014
DOI: 10.1016/j.psyneuen.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin induces social communication by activating arginine-vasopressin V1a receptors and not oxytocin receptors

Abstract: Arginine-vasopressin (AVP) and oxytocin (OT) and their receptors are very similar in structure. As a result, at least some of the effects of these peptides may be the result of crosstalk between their canonical receptors. The present study investigated this hypothesis by determining whether the induction of flank marking, a form of social communication in Syrian hamsters, by OT is mediated by the OT receptor or the AVP V1a receptor. Intracerebroventricular (ICV) injections of OT or AVP induced flank marking in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 27 publications
6
86
1
Order By: Relevance
“…X. laevis oocytes do not endogenously express OTRs (31), and OTR RNA was not coexpressed into the oocytes because we injected cells with RNA only for the α4, β, and δ GABA A R subunits. This finding is consistent with recent studies demonstrating that a range of OT functional effects rely on receptors other than the OTR (32)(33)(34)(35)(36). OT has, however, been found to alter the expression and function of GABA A Rs, albeit via an OTRmediated mechanism (37)(38)(39).…”
Section: Discussionsupporting
confidence: 92%
“…X. laevis oocytes do not endogenously express OTRs (31), and OTR RNA was not coexpressed into the oocytes because we injected cells with RNA only for the α4, β, and δ GABA A R subunits. This finding is consistent with recent studies demonstrating that a range of OT functional effects rely on receptors other than the OTR (32)(33)(34)(35)(36). OT has, however, been found to alter the expression and function of GABA A Rs, albeit via an OTRmediated mechanism (37)(38)(39).…”
Section: Discussionsupporting
confidence: 92%
“…Besides, other neurochemical systems could be acting in areas of the brain where OXTR density does not change (MA, MPOA), modulating the information received or sent to the AOB, VMH or LSv. It is also possible that OXT acts on V1AR to induce some of its behavioral effects (Song et al, 2014). Maternal behavior is the result of the coordinated action of a large neural network and multiple neurochemical systems (Olazábal et al, 2013), but local and region specific changes in OXTR might be critical to modify the processing of information by this large network.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents have found that the effects of OT on some social behavior and cognition (e.g., social communication) are mediated by AVP1A receptors (41,42). AVP1A receptors are densely located in the prefrontal, cingulate, pyriform, and entorhinal cortex, as well as the presubiculum and mammillary bodies, but are also found in the amygdala, bed nucleus of the stria terminalis, lateral septum, hypothalamus, and brainstem (43).…”
Section: Ot Reduces Brain Activity Evoked By Negative Emotional Stimulimentioning
confidence: 99%